If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3(4x + 2) = 96 Reorder the terms: 6x + 3(2 + 4x) = 96 6x + (2 * 3 + 4x * 3) = 96 6x + (6 + 12x) = 96 Reorder the terms: 6 + 6x + 12x = 96 Combine like terms: 6x + 12x = 18x 6 + 18x = 96 Solving 6 + 18x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 18x = 96 + -6 Combine like terms: 6 + -6 = 0 0 + 18x = 96 + -6 18x = 96 + -6 Combine like terms: 96 + -6 = 90 18x = 90 Divide each side by '18'. x = 5 Simplifying x = 5
| -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 | | 15x+3x-4=14whatisx | | 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 | | 9(x-2)=72 | | 3(2x-5)+6=4x+7 | | 4(x-3)=x-5 | | 5d+15-2d-10=11 | | 256+5546=x | | 8+3x=-4x+57 | | 4x+3(4x-6)=110 | | -3+4x=4(x-7)+25 | | -6x+8y=-22 | | -4x-1=-4-7x | | 5d+15-2d-10=10 | | 7x-4=6+6x | | 3x+6(x+8)=129 | | 4(t-3)=25 | | X-5=3(2x-1) | | 5s+4c=46 | | 3e+038= | | -7x+3=x-13 | | 5+y=2x | | -34-3x=-8x+46 |